Isothermal Crystallization Kinetics Effect on the Tensile Properties of PLA/PTT Polymer Composites - Tsou, C.-Y.; Wu, C.-L.; Tseng, Y.-C.; Chiu, S.-H.; Suen, M.-C.; Hung, W.S.; Tsou, C.-H. (Проблемы прочности, 2017)
A poly(lactic acid)/poly(trimethylene terephthalate) (PLA/PTT) composite was prepared by melt blending to improve the PTT crystallization rate. Morphology analysis of PLA/PTT fractured surfaces demonstrated the compatibility of its components. Thermogravimetric analysis revealed that the thermodegradation of a PLA/PTT sample was higher than that of PLA. Differential scanning calorimetry was used to evaluate the crystallization behavior. The Avrami equation described the isothermal crystallization kinetics. The Hoffman-Weeks parameters indicated that the PLA presence increased slightly the PTT nucleation. The tests of PLA, PTT, and PLA/PTT specimens in tension showed that a percent elongation of the PLA/PTT composite was between that of PLA and PTT; however, the tensile strength of the PLA/PTT composite was similar to that of PLA.